Autonomous weapons systems and the protection of the human person an international law analysis - Mauri, Diego (Elgar international law and technology, 2022)
roviding a much-needed study of the weapons paradox in the case of autonomous weapons, this book is a detailed and comprehensive account of the current debate over the use of autonomous weapons {u2013} should some form of regulation be applied or a total ban be enforced? How can compliance with existing rules be ensured? Can responsibility be properly allocated? To what extent do concepts such as u2018human dignityu2019 and u2018humanityu2019 provide legal guidance in coping with technology? This book tackles these momentous challenges and strives to provide sound answers by elaborating on international law and proposing normative solutions for current and future humanu2013machine interactions in this critical field. Diego Mauri expertly explains the complex new technological research involved in autonomous weaponry, with particular focus on technological developments that have elicited intense debates among diplomats, military experts, scientists, philosophers, and international lawyers.